The fatty acid composition in some economic and wild edible mushrooms in Turkey - Bengu, Aydın Sukru (Progress in Nutrition, 2020)
The aim of this study was to determine the fatty acid composition of different mushroom species collected from the Yozgat and Tokat region in Turkey. Fatty acid composition was determined in the mushroom species (Morchella elata, Macrolepiota procera, Lactarius delicious, Helvella lacunosa, Boletus edulis, Cantharellus cibarius, Bovista plumbea, Agaricus bisporus). The fatty acids copmpsition in mushrooms were identified and quantified by gas chromatography. The amounts % of fatty acids in species were different, Fatty acids with 14-24 carbons were occured in mushrooms samples linoleic acid was the major fatty acid detected in all species linoleic acid respectively in species ‘’ Bovista plumbea, Agaricus bisporus, Macrolepiota procera’’ were higher than other mushrooms. Percentage of linoleic acid (ω-6) in species varied from 10 % to 51 %. The other major fatty acids were respectively, palmitic, stearic, oleic acids other abundant fatty acids in the mushrooms. These four fatty acids were present in all of the mushrooms examined. The high level of docosadienoic acid (22:2) detected in Morchella elata is remarkable. When fatty acid composition results are compared as saturated and unsaturated, the fatty acid composition of the mushrooms showed that the unsaturated fatty acids are in higher proportions than the saturated fatty acids.